Sex-Specific Effect of the Dietary Protein to Carbohydrate Ratio on Personality in the Dubia Cockroach - Bouchebti, Sofia; Cortés-Fossati, Fernando; Vales Estepa, Ángela; Plaza Lozano, Maria; Calovi, Daniel S.; Arganda, Sara (My University, 2022)
Animal personality, defined by behavioral variations among individuals consistent over contexts or time, is shaped by genetic and environmental factors. Among these factors, nutrition can play an important role. The Geometric Framework of Nutrition has promoted a better understanding of the role of the macronutrient proportion in animal development, survival, reproduction, and behavior, and can help to disentangle its modulatory effect on animal personality. In this study, we investigated the effects of protein to carbohydrate (P:C) ratio in the personality of the cockroach Blaptica dubia. Newly emerged adults were fed over a period of eight weeks on five different diets varying in their P:C ratio and their diet consumption, mass variation, survival, exploratory behavior, and mobility were assessed. We found that females, unlike males, were able to regulate their nutrient intake and preferred carbohydrate-rich diets. Females also gained more body mass and lived longer compared to males. In addition, their behavior and mobility were not affected by the diet. In males, however, high-protein diets induced a bolder personality. We suggest that the sex-specific effects observed on both survival and behavior are related to the nutrient intake regulation capacity and might improve the species’ fitness in adverse nutritional conditions.
Keywords: nutrition; macronutrient proportion; exploratory behavior; Blaptica dubia; survival; 570